An evaluation of the module in group vs. individualized instruction for high school biology in a rural setting - Imperial, Emma Gubat 1950- (1978)
This study evaluated developed modular materials pertaining to the teaching of selected concepts in plant physiology to rural high school students enrolled in Science 2. It aimed to show the significant difference in student achievement between the experimental and control classes.